Self-Sovereign Identity in a Globalized World: Credentials-Based Identity Systems as a Driver for Economic Inclusion - Wang, Fennie; De Filippi, Primavera (Frontiers in Blockchain, 2020)
After introducing key concepts and definitions in the field of digital identity, this paper will investigate the benefits and drawbacks of existing identity systems on the road toward achieving self-sovereign identity. It will explore, in particular, the use of blockchain technology and biometrics as a means to ensure the “unicity” and “singularity” of identities, and the associated challenges pertaining to the security and confidentiality of personal information. The paper will then describe an alternative approach to self-sovereign identity based on a system of blockchain-based attestations, claims, credentials, and permissions, which are globally portable across the life of an individual. While not dependent on any particular government or organization for administration or legitimacy, credentials and attestations might nonetheless include government-issued identification and biometrics as one of many indicia of identity. Such a solution—based on a recorded and signed digital history of attributes and activities—best approximates the fluidity and granularity of identity, enabling individuals to express only specific facets of their identity, depending on the parties with whom they wish to interact. To illustrate the difficulties inherent in the implementation of a self-sovereign identity system in the real world, the paper will focus on two blockchain-based identity solutions as case studies: (1) Kiva's identity protocol for building credit history in Sierra Leone, and (2) World Food Programme's Building Blocks program for delivering cash aid to refugees in Jordan. Finally, the paper will explore how the combination of blockchain-based cryptocurrencies and self-sovereign identity may contribute to promoting greater economic inclusion. With digital transactions functioning as identity claims within an ecosystem based on self-sovereign identity, new business models might emerge, such as identity insurance schemes, along with the emergence of value-stable cryptocurrencies (“stablecoins”) functioning as local currencies.